2018
DOI: 10.1128/jb.00703-17
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Strategy Used by a Large c-di-GMP Network

Abstract: The genome encodes more than 50 proteins predicted to be involved in c-di-GMP signaling. Here, we demonstrated that, tested across 188 nutrients, these enzymes and effectors appeared capable of impacting biofilm formation. Transcriptional analysis of network members across ∼50 nutrient conditions indicates that altered gene expression can explain a subset of but not all biofilm formation responses to the nutrients. Additional organization of the network is likely achieved through physical interaction, as deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 55 publications
(69 reference statements)
1
43
0
Order By: Relevance
“…Next, we selected the CACHE domain-containing Pfl01_2295 and Pfl01_2297 proteins (Fig. 1A), both of which interact with LapD (20), to serve as controls to determine if other CACHE domains also respond to citrate to promote biofilm formation. For these studies, we used a P. fluorescens PfO-1 strain lacking four DGCs, referred to as Δ4DGC, which does not form a biofilm under our laboratory conditions; this low c-di-GMP producing strain was previously used to investigate c-di-GMP production by other P. fluorescens DGCs (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we selected the CACHE domain-containing Pfl01_2295 and Pfl01_2297 proteins (Fig. 1A), both of which interact with LapD (20), to serve as controls to determine if other CACHE domains also respond to citrate to promote biofilm formation. For these studies, we used a P. fluorescens PfO-1 strain lacking four DGCs, referred to as Δ4DGC, which does not form a biofilm under our laboratory conditions; this low c-di-GMP producing strain was previously used to investigate c-di-GMP production by other P. fluorescens DGCs (21).…”
Section: Resultsmentioning
confidence: 99%
“…actinidiae , the CACHE domain PscD (PDB ID: 5G4Z) binds glycolate, acetate, propionate, and pyruvate (22), indicating that CACHE domains allow for some promiscuity in their binding of ligands. GcbC has been shown to be part of a large signaling network, interacting with a phosphodiesterase and multiple dual domain containing proteins (20), thus also opening the possibility that different ligands sensed via the CACHE domain of GcbC could dictate which proteins interact with this DGC.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] To further complicate the scenario, genetic mutants in putative DGCs and/or PDEs showed unexpected phenotypes in terms of biofilm formation/dispersal. 5,6 A recent analysis on the regulation of the c-di-GMP network in Pseudomonas fluorescens Pf01 clearly showed that multifaceted regulatory strategies can take place to achieve the final phenotype, including combinations of ligand-mediated signals and/or transcriptional regulation. 5 Therefore, it appears that multiple signaling pathways could act together to obtain a unique c-di-GMP-dependent phenotype, and that different pathways could lead to the same output.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A recent analysis on the regulation of the c-di-GMP network in Pseudomonas fluorescens Pf01 clearly showed that multifaceted regulatory strategies can take place to achieve the final phenotype, including combinations of ligand-mediated signals and/or transcriptional regulation. 5 Therefore, it appears that multiple signaling pathways could act together to obtain a unique c-di-GMP-dependent phenotype, and that different pathways could lead to the same output. In this regard, the activity of DGCs and PDEs is often allosterically regulated by environmental/metabolic signals acting on upstream sensory domains.…”
Section: Introductionmentioning
confidence: 99%
“…In P. fluorescens SBW25, screens for wrinkly spreader biofilm phenotypes, which are associated with enhanced formation of cellulose-based matrix at the air-liquid (AL) interface, identified many DCGs and associated regulators involved in c-di-GMP homeostasis [47][48][49][50][51] . In P. fluorescens Pf0-1, a systematic survey of knockout mutants revealed that about a third of c-di-GMP-associated proteins exhibit strong biofilm phenotypes across many growth conditions whereas the remaining mutants exhibited weak phenotypes in only a small number of conditions 52 . However, the biological roles of most the c-di-GMPbinding proteins still remain to be characterized.…”
Section: Introductionmentioning
confidence: 99%